Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2478/ast-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

A Needs Assessment for Indigenous African Language-Based Programming Languages

Abstract: The development of an African native language-based programming language, using Yoruba as a case study, is envisioned. Programming languages based on the lexicons of indigenous African languages are rare to come by unlike those based on Asian and / or European languages. Availability of programming languages based on lexicons of African indigenous language would facilitate comprehension of problem-solving processes using computer by indigenous learners and teachers as confirmed by research results. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…According to Olatunji et al (2018), the development of PLs based on the lexicons of African indigenous languages will improve computer-based problemsolving processes by indigenous teachers and learners. This has also been shown by other research studies (Silva et al, 2020;Olatunji et al, 2019b;UNESCO 2007;Pflepsen 2011).…”
Section: Introductionsupporting
confidence: 85%
“…According to Olatunji et al (2018), the development of PLs based on the lexicons of African indigenous languages will improve computer-based problemsolving processes by indigenous teachers and learners. This has also been shown by other research studies (Silva et al, 2020;Olatunji et al, 2019b;UNESCO 2007;Pflepsen 2011).…”
Section: Introductionsupporting
confidence: 85%
“…Development of a programming language based on the lexicons of an African language, like Yoruba, is very much desirable and relevant, especially in Nigeria. This is attested to by the outcome of the needs survey carried out in which eighty-nine (89%) percent of respondents to the questionnaire used for needs assessment indicated their willingness to program or learn programming in their mother tongue, if one exists [14]. The successful development of the Yoruba-based programming language shows that lexical items of programming languages need not be borrowed exclusively from European and Asian languages, but can also be borrowed from most African indigenous languages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, development and adoption of NLPL will increase the functional load of their base languages; this will consequently reduce the chances of such languages going into extinction as predicted and feared in many circles [11]- [13]. Interestingly, in a related work, in a bid to ascertain the relevance and needfulness of NLPL, Olatunji et al [14] carried out a needs assessment survey for a NLPL through design and administration of structured questionnaire. It was reported that eighty-nine percent (89%) of the respondents to the questionnaire expressed eagerness and willingness to program or learn programming in a NLPL, if one exists.…”
Section: Introductionmentioning
confidence: 99%
“…As such, many educators have been promoting the use of local languages to preserve traditional culture and facilitate learning at school. In an attempt to provide a means of leaning programming using a native language, a research in [16], shows the high degree of relevance, usefulness and needfulness of a native language-based programming language as well as the worthwhileness of embarking on development of such a programming language. While this research move further to use one of the native language (Hausa) to prove it.…”
Section: Literature Reviewmentioning
confidence: 99%